2007
DOI: 10.1007/s11746-007-1049-1
|View full text |Cite
|
Sign up to set email alerts
|

Acyl Migration Kinetics of 2‐Monoacylglycerols from Soybean Oil via 1H NMR

Abstract: The acyl migration kinetics of neat 2-monoacylglycerol (2-MAG) to form 1-MAG was determined using 1 H NMR spectroscopy to monitor the b-proton integration ratios of the two species over time. 2-MAG was synthesized by the Novozym 435-catalyzed alcoholysis of soybean oil and isolated by solvent extraction or molecular distillation at a mole fraction (X 2-MAG ) of 0.94 relative to total MAG. The kinetics parameters of the neat 2-MAG acyl migration were investigated over the temperature range of 23-80°C. The 2-MAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 15 publications
7
93
0
1
Order By: Relevance
“…MAGs reach an equilibrium resulting in a sn2-MAG:sn1-MAG ratio of $1:9, while long-chain DAGs typically display a $1:2 ratio of sn1(3),2-DAG to sn1,3-DAG at equilibrium (Compton et al, 2007;Laszlo et al, 2008). It has been demonstrated that acid and base impurities, and enzymatic support carrying charges catalyze acyl-migration (Fureby et al, 1996).…”
Section: Lipase Screening In Batch Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…MAGs reach an equilibrium resulting in a sn2-MAG:sn1-MAG ratio of $1:9, while long-chain DAGs typically display a $1:2 ratio of sn1(3),2-DAG to sn1,3-DAG at equilibrium (Compton et al, 2007;Laszlo et al, 2008). It has been demonstrated that acid and base impurities, and enzymatic support carrying charges catalyze acyl-migration (Fureby et al, 1996).…”
Section: Lipase Screening In Batch Reactionsmentioning
confidence: 99%
“…In our work, the sn2-MAG produced are not converted by this mechanism, suggesting that the reaction media and enzymatic supports do not offer ideal conditions for acyl migration (dry medium, non-water-miscible alcohols). Compton et al (2007) and Laszlo et al (2008) demonstrated that at 40°C and in the absence of catalyzing agent, the acyl-migration is relatively slow: only 20% conversion of sn2-MAG into sn1(3)-MAG and sn1 (3),2-DAG into sn1,3-DAG were reached in $120 and 200 h respectively. Acyl migration was accelerated at 60°C, and 20% conversion was attained in 24 h for MAG and $30 h for DAG.…”
Section: Lipase Screening In Batch Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other CH2 groups from the DEG structure generate a group of poorly resolved signals in the range of 3.5-3.75 ppm, restricting their use in quantitative analysis. Compton showed that the 1H NMR spectrum is a useful tool to quantify MAG and DAG 23 . The remaining acylglycerols in the DEG ester products, such as MAG and DAG, showed signals near 3.9, 4.05 and 4.09 ppm, while TAG showed a signal near 5.23 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the low acyl migration rate was contributed to the low reaction temperature. It has been reported that rate constants of 2-MAGs in a solventfree system at 23 and 60°C are 0.00018 and 0.00752 h À1 , respectively (Compton et al, 2007). Thus, the reaction temperature dramatically affects the acyl migration rate.…”
Section: Acyl Migration Of 2-mags During Enzymatic Transesterificatiomentioning
confidence: 98%